청소년의 학업 및 가족갈등 스트레스가 인터넷 중독에 미치는 영향 -스트레스대처능력의 조절효과 중심으로 - 아영아; Young Ah Ah; 정원철; Weon Cheul Jeong (청소년복지연구, 2010)
본 연구는 부산지역 중·고등학생 2,061명을 대상으로 청소년들이 경험하는 가족갈등스트레스 및 학업스트레스와 청소년의 인터넷 중독과의 관련성을 살펴본후, 스트레스대처능력이 이들 변수의 관계에서 조절효과를 가지는지를 살펴보기 위해 설계되었다. 연구 결과, 가족갈등스트레스, 학업스트레스, 스트레스대처능력은 인터넷 중독을 예측하는 중요한 인자로 확인되었다. 또한 가족 및 학업스트레스와 인터넷 중독 관계에서 스트레스대처능력의 조절효과를 알아본 결과, 학업스트레스와 인터넷 중독의 관계에서 스트레스대처능력은 조절효과를 보이지 않은 반면, 가족갈등스트레스는 스트레스대 처능력과 상호작용하여 인터넷 중독을 조절하는 것으로 나타났다. 조절효과의 방향 면에서 스트레스 대처능력이 높은 집단은 가족갈등스트레스가 높은 상황에서도 인터넷 중독이 낮아짐을 알 수 있었다. 반면, 스트레스대처능력이 낮은 집단은 가족갈등스트레스가 높을수록 인터넷 중독수준이 높아지고 있음을 알 수 있다. 또한 조절효과의 강도면에서도 스트레스대처능력이 낮은 집단은 높은 집단에 비해 가족갈등스트레스가 같은 수준에서도 인터넷 중독수준이 높은 것으로 나타났으며, 특히 가족갈등스트레스가 높은 상황에서는 인터넷 중독 수준의 차이가 더욱 극명하게 나타나는 특성을 보였다. 이러한 결과는 청소년들이 가족갈등스트레스를 높게 인식하여도 스트레스대처능력이 높으면 인터넷 중독이 오히려 낮아지는 특성을 보여 스트레스대처능력의 향상이 가족갈등스트레스를 보호할 수 있음을 보여준 것이다. 따라서 가족갈등스트레스를 많이 인식하는 청소년일지라도 스트레스대처능력을 향상시키는 개입이 이루어진다면 청소년의 인터넷 중독의 위험을 상당부분 완화시킬 수 있음을 본 연구결과는 보여주었다. This study explored whether stress coping strategies moderated the relation of academic and family conflict stress and adolescents` internet addiction. The data were collected from 2,061 of students in the middle and high school located in Pusan. The results of analysis are as follows: First, it was proved that family conflict, academic stress played as inducting factors to internet addiction. Second, the results indicated that stress coping strategies moderated on the relation between family conflicts and internet addiction. In addition, in the direction of the moderating effect, it was found out that in the group of high ability to cope with stress, Internet addiction has been lowered in high-family conflict stress situation. In contrast, the group of low ability to cope with stress, higher family conflict increased the level of Internet addiction. In addition, in terms of the strength of the moderating effect, the high level group of coping with stress was higher internet addiction level than low level group at the same level of family conflict stress, especially in high-family conflict stress situation, the more the difference between the level of internet addiction clearly showed the characteristics appear. These results show that young people can improve your ability to cope with stress, family conflicts can be mitigated even though young people perceived family conflict highly. Thus, this study showed Internet addiction can mitigate a significant portion of the risk, if done interventions to improve coping skills, although young people are aware a lot of family conflict stress.